Differently linked fluorene-carbazole triads for light amplification. (December 2015) - Baronas, Paulius; Kazlauskas, Karolis; Kreiza, Gediminas; Jankauskas, Vygintas; Tomkeviciene, Ausra; Simokaitiene, Jurate; Grigalevicius, Saulius; Grazulevicius, Juozas V.; Jursenas, Saulius
Abstract: The impact of linking topology of fluorene-carbazole triads on amplified and spontaneous emission as well as on concentration quenching of emission and charge carrier mobility, i.e. on the properties essential for organic laser application, was investigated. Deep-blue-emitting triads featuring 2, 7- substitution pattern and bulky alkyl moieties expressed high emission quantum yield (0.8–0.9) and low concentration quenching, which benefited in attaining large radiative decay rates (∼10 9 s −1 ) and rather low amplified spontaneous emission (ASE) threshold (down to 9 kW/cm 2 ) for compound concentrations up to 3 wt % in polymer matrix. Most of the triads expressed carrier drift mobilities close to 10 −2 cm 2 /(V·s) in amorphous films pointing out efficient charge transport essential for reducing threshold current density for lasing. The impact of the position (central or side) of fluorene/carbazole moieties in the triad or the linking position (C-2 or C-3) of the side groups on the ASE threshold and carrier mobility was found to be of little significance. However, a huge advantage of 2, 7- substitution pattern over 3, 6- pattern for the triads in terms of ASE performance was demonstrated. Importantly, the obtained results suggested a possible trade-off between ASE threshold reduction and carrier mobility enhancement, which may hamper the realization of electrically-driven lasing in organic amorphous films. Highlights: Fluorene-carbazole triads showed high emission quantum yield and radiative decay rate. The triads expressed low amplified emission threshold and high carrier mobility. Low concentration quenching of emission ensured low ASE threshold at high concentrations. Advantage of 2, 7- substitution pattern vs 3, 6- for light amplification is demonstrated. Trade-off between ASE threshold and carrier mobility of the triads is revealed.